Influence of Heat Treatment and Microfiltration on the Milk Proteins Properties - Silvani Verruck; Saionara Sartor; Flávia Buss Marenda; Eulália Lopes da Silva Barros; Callebe Camelo-Silva; Maria Helena Machado Canella; Elane Schwinden Prudencio (Advances in Food Technology and Nutrition Sciences, 2019)
Heat treatments are the established food technology for commercial processing of milk. However, degradation of valuable nutrients in milk (as proteins) and its sensory characteristics occur during these processes due to substantial heat exposure. The most important reactions that occur during milk heat treatment are the whey proteins denaturation, its interactions with the casein micelles and aggregation/dissociation of the casein micelles. Microfiltration represents an emerging food processing technology allowing gentle milk preservation at lower temperatures for similar, or better, nutritive value, microbial removal, and shelf stability. Thus, the aim of this work is to review the existing studies on the effects of microfiltration on milk proteins by comparing with the effects of heating treatments.